Studi Spektroskopi FTIR untuk Karakterisasi Kimia Fisik Fluida Mata Air Panas Di Desa Tempang Kabupaten Minahasa - Geraldy Wawondatu; Donny R. Wenas; Farly R. Tumimomor (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2022)
The increasing population of the world's population results in the need for energy to continue to increase, therefore the Indonesian government develops energy outside of fossil fuels, one of which is geothermal. Geothermal is one of the alternative energy source that is relatively new and renewable and can be renewed because production waste in the form of water is re-injected and produces a recycle process that allows sustainability. Geological surveys, geochemical surveys, and geophysical surveys are characterizations that need to be carried out in describing geothermal potential. The purpose of this study was to determine the type of fluid and molecular functional groups of hot springs in Tempang Village, Minahasa Regency. With the geochemical method using a spectrophotometer and FTIR (Fourier Transform Infra Red) spectroscopy, it is known that the type of fluid in the hot springs in Tempang Village is Bicarbonate (HCO3) type with a content of 69 mg/L and the molecular functional group is O-H and C=O.